(untitled) (The Research of Medical Science Review, 2025)
The study therefore undertaken at the CSSD of a tertiary care hospital a prospective cross-sectional study conducted over 6 months. A total of 196 reusable surgical instruments were categorized into two groups: Ultrasonic cleaner – Group A and Washer Disinfector – Group B. Observations of pre-treatment and post- treatment status of the instruments regarded cleanliness of the surface, corrosion visible on the surface, the brightness of the surface as well as alignment were recorded. Questionnaires were completed using scores and data was analyzed with (SPSS), version 25. The results showed that ultrasonic cleaners significantly reduced the levels of dirt from 90.0% to 28.0% and corrosion from 69.5% to 5.0%. Other parameters in washer disinfectors were raised with dirt reduced to 15.0% and corrosion to 18.5%. Ultrasonic cleaners provided a 91.0% restoration of instrument surface shine whereas washer disinfectors achieved a slightly higher restoration rate of 93.2%. There was improvement in the alignment of the instruments on washer disinfectors, 82.9% proper alignment after cleaning against ultrasonic cleaners 86.3%. Rust was present more frequently in the washer disinfector group 36.0% than in the ultrasonic cleaner group 18.0%. This work examines that ultrasonic cleaners are highly effective in removing dirt and corrosion especially for instruments with compact structures while washer disinfectors are effective in maintaining instruments’ alignment and surface shine. The best practice suggested to improve the cleaning operations is the fusion of qualities of both approaches.